Auditing in the Digital Era: Challenges and Opportunities for Auditor - Rahman, Fadhil; Putri, Gina; Wulandari, Dina; Pratama, Dedi; Permadi, Eka (Manunggal Halim Jaya, 2021)
This qualitative study explores the challenges and opportunities faced by auditors in the digital era, focusing on data privacy concerns, cybersecurity threats, skills shortages, and regulatory complexities. Grounded theory methodology was employed to analyze literature encompassing auditing in the digital environment. Data collected from various scholarly sources were systematically reviewed, synthesized, and analyzed using open and axial coding techniques. The findings reveal that auditors encounter significant challenges related to navigating stringent data privacy regulations such as the GDPR and CCPA, addressing evolving cybersecurity threats, mitigating skills shortages in critical areas like data analytics and cybersecurity, and complying with dynamic regulatory frameworks like ISAs, GAAS, and SOX. However, amidst these challenges, auditors also have opportunities to enhance audit quality through advanced technologies like data analytics and AI, expand their scope of assurance services, and improve client collaboration using digital communication tools. The study underscores the importance of proactive measures to address skills shortages, foster collaboration between auditors and stakeholders, and adapt audit methodologies to the digital landscape. Overall, the research provides insights into the complex interplay between auditors, digital technologies, and regulatory environments, offering implications for audit practice, education, and research.